Making fatty girl cakes: food and resistance in a women's prison - Smoyer, Amy B. (The Prison Journal, 2016)
This article builds on existing knowledge of inmate resistance by analyzing formerly incarcerated women's narratives about prison food. Participants described trying to secure extra cafeteria portions, hoarding food, smuggling and stealing food, and cooking and eating in the cellsall to resist prison power and gain some control over their lives by managing what, how, when, and with whom they ate. These data shed light on prison life and suggest changes to food policy to curb inmate resistance and bolster the rehabilitative potential of correctional facilities.
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/095-837-797-757-693 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.swk; food; prisoners; resistance; women